Sample size to identify the impact in a discontinuous regression - Valderrama Torres, José (2013)
The termination of the sample size necessary to identify the impact in a Discontinuous Regression is presented analytically. In particular, the scenario of violation of the assumption of independence of the errors caused when the data are distributed in clusters is considered.